A Bibliometric Analysis of Pulmonary Alveolar Proteinosis From 2001 to 2021 - Liu, Shixu; Cui, Xiangning; Xia, Kun; Wang, Dandan; Han, Jing; Yao, Xiaoyan; Liu, Xiaohong; Bian, Lingjie; Zhang, Jinzhi; Li, Guangxi (Frontiers in Medicine, 2022)
Background Pulmonary alveolar proteinosis (PAP) is a rare syndrome first described by Rosen et al. in 1958. Despite our considerably evolved understanding of PAP over the past decades, no bibliometric studies have been reported on this field. We aimed to analyze and visualize the research hotspots and current trends of the PAP research field using a bibliometric analysis to help understand the future development of basic and clinical research. Methods The literature regarding PAP was culled from the Web of Science Core Collection (WoSCC) database. Data were extracted from the relevant articles and visually analyzed using CiteSpace and VOSviewer software. Results Nine hundred and nine qualifying articles were included in the analysis. Publications regarding PAP increased over time. These articles mainly come from 407 institutions of 57 countries. The leading countries were the USA and Japan. University of Cincinnati (USA) and Niigata University (Japan) featured the highest number of publications among all institutions. Bruce C Trapnell exerts a significant publication impact and has made the most outstanding contributions in the field of PAP. American Journal of Physiology-Lung Cellular and Molecular Physiology was the journal with the most publications, and American Journal of Respiratory and Critical Care Medicine was the most commonly cited journal. All the top 5 co-cited journals belong to Q1. Keyword citation bursts revealed that inflammation, deficiency, tissue resident macrophage, classification, autoimmune pulmonary alveolar proteinosis, sarcoidosis, gm csf, high resolution ct, and fetal monocyte were the emerging research hotspots. Conclusion Research on PAP is prosperous. International cooperation is also expected to deepen and strengthen in the future. Our results indicated that the etiology and pathogenesis of PAP, current and emerging therapies, especially the novel pathogenesis-based options will remain research hotspots in the future.